MiR-216a-3p inhibits the cytotoxicity of primary natural killer cells - Abdelbary, Rowan; Ragheb, Manon; El Sobky, Shereen A.; El-Badri, Nagwa; Aboud, Nourhan; Tawheed, Ahmed; Gomaa, Asmaa; Zidan, Mona; Aziz, Ramy K.; Abouzid, Abd Elrahman; Salah, Radwa Ayman; El-Kassas, Mohamed; et al. (Frontiers in Oncology, 2025)
IntroductionThe role of miRNAs in regulating variable molecular functions has been sought by scientists for its promising utility in regulating the immune response and, hence, in treating various diseases. In hepatocellular carcinoma (HCC) specifically, a reduction in the number and efficiency of circulating and intrahepatic natural killer (NK) cells has been reported. Our project aims to investigate the role of miR-216a-3p in the regulation of NK cell cytotoxicity, especially since it plays a tumor suppressor role in the context of HCC.MethodsTo achieve our aim, we isolated NK cells from the whole blood of 86 patients with HCC and 23 healthy controls. We assessed the expression profile of miR-216a-3p in NK cells of patients and controls. Furthermore, we induced the expression of miR-216a-3p in NK cells isolated from healthy controls, followed by measuring the release of interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), perforins (PRF) and granzyme B (GrB) using ELISA as well as NK cells cytolytic activity against Huh7 cells using lactate dehydrogenase (LDH) cytotoxicity assay. After that, we performed an in silico analysis to understand the mechanistic regulation imposed by miR-216a-3p on NK cells to study its impact on one of its potential downstream targets.ResultsOur results have indicated that miR-216a-3p has higher expression in NK cells of patients with HCC, and simulating this elevated expression pattern via forcing miR-216a-3p expression in normal NK cells has negatively impacted the release of TNF- α, IFN- γ, GrB, and PRF. Consequently, a decrease in cell cytolysis was observed. Our in silico analysis revealed that the predicted downstream targets of miR-216a-3p are enriched in the FOXO-signaling pathway. Among those targets is FOXO-1, which has been reported to play a role in NK cell maturation. Thus, we evaluated FOXO-1 expression upon mimicking miR-216a-3p in control NK cells that showed significant downregulation of FOXO-1 on both RNA and protein levels.ConclusionIn conclusion, we report miR-216-3p as a negative regulator of NK cell cytotoxicity.